2020
DOI: 10.1017/s1355617720000430
|View full text |Cite
|
Sign up to set email alerts
|

REM Sleep Behavior Disorder in Parkinson’s Disease: Effects on Cognitive, Psychiatric, and Functional outcomes

Abstract: Objective: Rapid eye movement sleep behavior disorder (RBD) affects 33–46% of patients with Parkinson’s disease (PD) and may be a risk factor for neuropsychological and functional deficits. However, the role of RBD on neuropsychological functioning in PD has yet to be fully determined. We, therefore, examined differences in neurocognitive performance, functional capacity, and psychiatric symptoms among nondemented PD patients with probable RBD (PD/pRBD+) and without (PD/pRBD−), and healthy comparison part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Studies by Bargiotas et al [ 37 ] found that patients with PD who have RBD had a higher probability of developing apathy and higher AS scores, thus indicating that RBD may be a potential risk factor for apathy. This is consistent with the conclusion of Mahmood et al [ 38 ]. Because it is relatively easy to identify RBD in the early stages of the disease or even in the prodromal stage, its presence may facilitate early clinical identification of apathetic patients.…”
Section: Discussionsupporting
confidence: 94%
“…Studies by Bargiotas et al [ 37 ] found that patients with PD who have RBD had a higher probability of developing apathy and higher AS scores, thus indicating that RBD may be a potential risk factor for apathy. This is consistent with the conclusion of Mahmood et al [ 38 ]. Because it is relatively easy to identify RBD in the early stages of the disease or even in the prodromal stage, its presence may facilitate early clinical identification of apathetic patients.…”
Section: Discussionsupporting
confidence: 94%
“…However, even if increasing evidence have demonstrated the detrimental effect of a rapid cognitive decline on several adverse events with this method, including functional disability, hospitalization, nursing home admission, regional brain atrophy, and mortality [14][15][16], most existing studies failed to take initial cognitive function into account [14,15]. Furthermore, although cognitive deterioration has been reported to be associated with several functional deficits such as frailty [17], falls [18], rapid eye movement behavior disorders (RBD) [19], depression [20], motor cognitive risk syndrome (MCR) [21] and etc., it remains undetermined whether cognitive ageing trajectory is associated with these functional deficits as well. Likewise, previous efforts which probed into factors shaping cognitive ageing trajectories were limited by small sample size, specific risk factors, or conflicting results primarily from western populations [8,9,11,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the prodromal phase have focused only on individuals with iRBD, omitting those without iRBD (35,36). This approach misses a significant subset of PD patients who will never have iRBD, thereby limiting a comprehensive understanding of the prodromal phase (37,38). Our study addresses this gap by incorporating a hyposmic cohort, enriched by the prerequisite of abnormal DAT-SPECT imaging for enrolment.…”
Section: Discussionmentioning
confidence: 99%